1996
DOI: 10.1152/ajpheart.1996.271.6.h2717
|View full text |Cite
|
Sign up to set email alerts
|

ATP: the red blood cell link to NO and local control of the pulmonary circulation

Abstract: Recently, we reported that rabbit red blood cells (RBCs) were required for the expression of nitric oxide (NO) activity on pulmonary vascular resistance (PVR) in rabbit lungs. Here, we investigate the hypothesis that RBCs participate in the regulation of PVR via release of ATP in response to mechanical deformation that, in turn, evokes vascular NO synthesis. We found that rabbit and human RBCs, but not dog RBCs, release ATP in response to mechanical deformation. To determine the contribution of this ATP to NO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
297
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(313 citation statements)
references
References 0 publications
16
297
0
Order By: Relevance
“…We openly acknowledge this limitation in our manuscript and are working to develop a selective antagonist. However, with respect to hypoxic vasodilation in resistance vessels, a number of important observations support our data: (1) perfusion of isolated resistance vessels with a buffer lacking erythrocytes fails to elicit vasodilation when extraluminal oxygen tension is reduced 11 ; (2) perfusion of isolated skeletal muscle resistance vessels with erythrocytes not capable of releasing ATP does not elicit vasodilation in response to this stimulus 12,13 ; (3) rescuing low O 2 -induced ATP release from diseased erythrocytes restores vasodilation when extraluminal oxygen tension is reduced. 12 These studies to date have not been performed within contracting muscle, and although this would be technically difficult, is certainly an area in need of future investigation.…”
Section: The Age-old Tale Of Skeletal Muscle Vasodilation: New Ideas supporting
confidence: 80%
“…We openly acknowledge this limitation in our manuscript and are working to develop a selective antagonist. However, with respect to hypoxic vasodilation in resistance vessels, a number of important observations support our data: (1) perfusion of isolated resistance vessels with a buffer lacking erythrocytes fails to elicit vasodilation when extraluminal oxygen tension is reduced 11 ; (2) perfusion of isolated skeletal muscle resistance vessels with erythrocytes not capable of releasing ATP does not elicit vasodilation in response to this stimulus 12,13 ; (3) rescuing low O 2 -induced ATP release from diseased erythrocytes restores vasodilation when extraluminal oxygen tension is reduced. 12 These studies to date have not been performed within contracting muscle, and although this would be technically difficult, is certainly an area in need of future investigation.…”
Section: The Age-old Tale Of Skeletal Muscle Vasodilation: New Ideas supporting
confidence: 80%
“…The answer may also lie in the vascular endothelium. Indeed, Sprague et al 29 recently found that human RBCs release ATP in response to mechanical deformation; this ATP evokes the release of NO, thereby lowering pulmonary vascular resistance. Endothelial activation in this manner should attenuate platelet aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…ATP can be released from endothelium in response to increases in shear stress (Bodin et al, 1991) and from perivascular nerve terminals (Ralevic & Burnstock, 1998;Burnstock & Kennedy, 1986). InÂŻammatory mediators, ischaemia, and damage to blood vessels also cause ATP release from endothelial cells, neutrophils, cardiomyocytes, erythrocytes and platelets (Borst & Schrader, 1991;Born & Kratzer, 1984;Bodin & Burnstock, 1998;Pearson & Gordon, 1985;Yang et al, 1994;Bergfeld & Forrester, 1992;Gordon, 1986;Ralevic & Burnstock, 1991;1998;Sprague et al, 1996;Olsson & Pearson, 1990). ATP is rapidly broken down to adenosine by endothelial ectonucleotidases (Pearson & Gordon, 1985).…”
Section: Introductionmentioning
confidence: 99%